Assessing the readability of open data portals: a case study of Open Data Pakistan - Warraich, Nosheen Fatima; Rasool, Tayyba (Malaysian Journal of Library and Information Science, 2023)
Open data portals have been implemented in numerous countries to provide accessible, usable, and reproducible data. This study aims to assess the readability of datasets from Open Data Pakistan. Using the URL (https://opendata.com.pk/) in an online readability checking tool, six well-known readability formulas were employed, including Flesch Kincaid Reading Ease, Flesch Kincaid Grade Level, Gunning Fog Score, Smog Index, Coleman Liau Index, and Automated Readability Index. The average score of each formula was calculated to analyze the standard readability of the open data portal. Additionally, the website was explored to evaluate the overall status of open datasets, showcases, and features like "Connect" on Open Data Pakistan. The findings indicated that the Open Data Pakistan website has a reading difficulty, scoring an average of 47.4 out of 100, making it challenging for the general public to read. However, the overall analysis suggested that the readability status of open data in Pakistan is satisfactory. These results offer insights into improving the readability of open data for enhanced citizen participation and informed decision-making. Moreover, the study has implications for policymakers and stakeholders regarding the readability of Open Data Pakistan, emphasizing the importance of considering readability in open data publication policies and guidelines, with a recommendation to decrease the percentage of open data portals categorized as hard to read.